The effect of work-related stress on employee well-being with ethical leadership as a moderator among back-office bankers - Ramadani, Diah Putri; Sari, Reza Lidia (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2025)
The rapid development of the global financial services sector has brought new challenges for bank employees, including an increase in work-related stress. This study investigates the impact of work-related stress on employee well-being and whether ethical leadership can moderate this relationship. An online cross-sectional survey consisted of three instruments: the Health and Safety Executive Work-related Stress Scale, Employee Well-being Scale, and the Ethical Leadership Questionnaire. The survey was administered to 96 back-office employees in the bank, all of whom had a minimum of one year of tenure and were selected using an accidental sampling technique. Data analysis was conducted using moderated regression analysis with Jamovi for Windows, version 2.3.28. The results showed a significant negative impact of work-related stress on employee well-being, while ethical leadership had a positive effect on it. However, ethical leadership was not a moderator in the relationship between work-related stress and employee well-being. These findings highlight the importance of stress management programs and the promotion of ethical leadership in promoting employee well-being within the banking sector.